THE RELATIONSHIP BETWEEN MATERNAL KNOWLEDGE AND ATTITUDE AND THE INCIDENCE OF STUNTING - Riandra, Ni Putu Indah Kusumadewi; Wijaya, Putu Austin Widyasari; Trisnia, Putu Ayunda (JURNAL WIDYA MEDIKA, 2026)
Children under five years old are the most vulnerable group to nutritional problems. Undernourished children are at risk of reduced intelligence quotient, decreased immunity, lower productivity, mental and emotional health problems, and growth failure. Various maternal factors, including knowledge, and attitude influence this nutritional problem among children under five. This study aimed to analyze the relationship between maternal knowledge level and attitude and the incidence of stunting among children under five in Bayung Gede Village, Kintamani District, Bangli, Bali. This observational study employed a cross-sectional design involving 48 mothers with children under the age of five, selected using consecutive sampling. Data were collected using a structured questionnaire to assess maternal knowledge and attitude toward stunting, while children’s nutritional status was determined based on height-for-age measurements. Statistical analysis was performed using the chi-square test. The results showed that 30 (62.5%) of mothers had good knowledge, and 29 (60.4%) demonstrated a positive attitude toward stunting prevention. A significant relationship was found between maternal knowledge and stunting incidence, with children of mothers who had poor knowledge being more likely to experience stunting. Maternal attitude was also significantly associated with stunting incidence, indicating that a negative attitude increased the likelihood of stunting. These findings suggest that maternal knowledge and attitude play important roles in the occurrence of stunting. Strengthening educational interventions and improving access to health information for mothers are essential strategies to reduce stunting incidence among children under five.